2003
DOI: 10.1580/1080-6032(2003)014[0020:ceodah]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Dexamethasone at High Altitude☆

Abstract: These data show a trend toward decreased cognitive deficits in subjects pretreated with dexamethasone. One possibility for this trend is that cognitive deficits in otherwise asymptomatic subjects exposed to high altitude are caused by subclinical cerebral edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Comparing Dexamethasone with Acetazolamide or placebo, the use of Dexamethasone significantly reduced the incidence of AMS and the severity of symptoms, without affecting physical or mental aspects (p<0.05) (Ellsworth et al,1987;Ellsworth et al,1991). A study showed a decrease of cognitive deficits in asymptomatc subjects caused by subclinical cerebral oedema (Lafleur et al,2003).…”
Section: Glucocorticosteroidsmentioning
confidence: 99%
“…Comparing Dexamethasone with Acetazolamide or placebo, the use of Dexamethasone significantly reduced the incidence of AMS and the severity of symptoms, without affecting physical or mental aspects (p<0.05) (Ellsworth et al,1987;Ellsworth et al,1991). A study showed a decrease of cognitive deficits in asymptomatc subjects caused by subclinical cerebral oedema (Lafleur et al,2003).…”
Section: Glucocorticosteroidsmentioning
confidence: 99%
“…Unlike acetazolamide, which prevents symptoms of AMS by assisting in pre-acclimatization, dexamethasone decreases cerebral edema by preserving endothelial integrity and preventing cerebral vascular leaking. 18,19 These properties of dexamethasone have led to interest in clinical trials for HAI prophylaxis. In addition, the antiemetic and mood-enhancing effects of dexamethasone could also explain the effectiveness of dexamethasone for HAI prevention.…”
Section: Dexamethasonementioning
confidence: 99%
“…Acetazolamide has been shown to enhance exercise and cerebral oxygenation at altitude. 6,7 Dexamethasone improves cognitive performance 8,9 and exercise capacity 10,11 at altitude. That is strong evidence that these are performance-enhancing drugs.…”
mentioning
confidence: 99%